Effect of Polyporaceae fungi on growth and cellulose degradation of Ganoderma spp. isolated from Basal Stem Rot (BSR) diseas - Ili Bazilah, Abdul Razak (Universiti Malaysia Sarawak (UNIMAS), 2006)
Interaction of three isolates of Ganoderma spp.; Ganoderma sp. 9, Ganoderma sp. 10, Ganoderma sp. II isolated from Basal Stem Rot of palms with 20 isolates of Polyporaceae were tested. The interaction studies were done by inoculating the pathogenic Ganoderma simultaneously, one week earlier and one week late than the Polyporaceae on potato dextrose agar in the same Petri dish. Eight isolates of the Polyporaceae; Trametes versicolor, unknown sp., Ganoderma sp., Amauroderma perplexum, Phellinus sp., Polyporus sp., Daedalea sp. and Micropus Jlabelliform were able to retard the growth of the pathogenic Ganoderma. Effect of crude extract of the eight isolates of Polyporaceae which were found effectively inhibit the growth of the pathogenic Ganodenna during the interaction study was also observed. There were significant effect of the crude extracts from the Polyporaceae on the growth of the pathogenic Ganoderma when 30% concentration was used. Study on cellulose degradation of the pathogenic Ganoderma in the present of the eight Polyporaceae species which showed inhibiting effects in the interaction study was also determined. All the eight isolates of the Polyporaceae were significantly reduced the cellulose degradation activity of the pathogenic Ganoderma.